2017
DOI: 10.1002/adhm.201601252
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Kupffer Cell Autophagy Abrogates Nanoparticle‐Induced Liver Injury

Abstract: The possible adverse effects of engineered nanomaterials on human health raise increasing concern as our research on nanosafety intensifies. Upon entry into a human body, whether intended for a theranostic purpose or through unintended exposure, nanomaterials tend to accumulate in the liver, leading to hepatic damage. A variety of nanoparticles, including rare earth upconversion nanoparticles (UCNs), have been reported to elicit hepatotoxicity, in most cases through inducing immune response or activating react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Meanwhile, continuous investigations on intricate interactions between nanomaterials and biological systems will uncover underlying mechanisms of "black boxes" after the bio-distribution of NPs administered to the body, leading to new strategies for manipulating physiological conditions to maximize the impact of nanotherapeutics on disease treatments [185][186][187][188] . Moreover, understanding molecular interactions among NP components (ie, nanomaterials, loaded drugs) within the nanostructure can shed light on valuable mechanisms leading to the rational design of drug delivery systems with desirable physicochemical properties for precisely controlled drug loading and release [51,173,[189][190][191] .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Meanwhile, continuous investigations on intricate interactions between nanomaterials and biological systems will uncover underlying mechanisms of "black boxes" after the bio-distribution of NPs administered to the body, leading to new strategies for manipulating physiological conditions to maximize the impact of nanotherapeutics on disease treatments [185][186][187][188] . Moreover, understanding molecular interactions among NP components (ie, nanomaterials, loaded drugs) within the nanostructure can shed light on valuable mechanisms leading to the rational design of drug delivery systems with desirable physicochemical properties for precisely controlled drug loading and release [51,173,[189][190][191] .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…There are some studies confirming that hepatocyte toxicity caused by nanomaterials was mediated by autophagy. (Fan et al, ; Paesano et al, ; Zhang et al, ; Zhu et al, ). Studies have shown that low‐dose (3 μg ml −1 ) CdS QDs can lead to upregulation of autophagy related genes ATG3, ATG7, ATG13 and ATG14, whereas in high doses (14 μg/ml), there is no such inducement effect in HepG2 cells (Paesano et al, ), which suggest the significance of autophagy in preventing intracellular damage.…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
“…There are some studies confirming that hepatocyte toxicity caused by nanomaterials was mediated by autophagy. (Fan et al, 2016;Paesano et al, 2016;Zhang et al, 2017;Zhu et al, 2017). Studies have shown that low-dose (3 μg ml −1 ) CdS QDs can lead to upregulation of autophagy related genes ATG3, ATG7, ATG13 and ATG14, whereas in high doses (14 μg/ml),…”
Section: Elevated Intracellular Ca 2+ Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the locality of the KCs in the wall of sinusoids, this subpopulation might act as a barrier to the nonsoluble NMs, preventing them from reaching the hepatocytes. In addition, activated KCs are one of the most important hepatic cell populations in modulation and governance of the organs immune response both in health and disease states (Bottcher, Knolle, and Stabenow 2011;Kermanizadeh et al 2014a;Tiegs and Lohse 2010;Zhu et al 2017).…”
Section: Introductionmentioning
confidence: 99%